EP003/#1114 Identification of molecular targets and pathways for improving endometrial cancer racial disparities. (4th December 2022) - Borden, Lindsay; Javadian, Pouya; Kennedy, Amy; Xu, Chao; Sjoelund, Virginie; Benbrook, Doris
Abstract : Objectives: Identify proteins present at significantly different levels in endometrial cancer specimens across 4 racial groups to direct future therapy. Methods: Proteins extracted from endometrioid endometrial cancer specimens of women who self-identified as Black, American Indian, or White (N=12 each), or Asian (N=10) were measured by Tandem Mass Tag liquid chromatography-tandem mass spectrometry. Patients were matched for age and body mass index. Significant differences in protein levels were identified by ANOVA after adjustment of the first principal component and evaluated by Ingenuity Pathway Analysis. Drug effects on human Ishikawa endometrial cancer cells were evaluated using an MTT assay. Results: The only patient characteristics significantly different across racial groups were higher rates of diabetes in Blacks and hypertension in Whites. Fifty-eight proteins exhibited significant differences across all groups. The most significant pathways identified to be regulated by proteins significantly different in non-Whites compared to Whites are regulators of protein synthesis. Trametinib and 2-deoxyglucose inhibition of mitogen-activated protein kinase 3 and hexokinase-2, which were significantly upregulated in specimens from Blacks compared to Whites, reduced growth of endometrial cancer cells with half-maximal inhibitory concentrations of 3 uM and 3 mM, respectively, but did not interact synergistically. Conclusions: This study demonstrated significantly different protein expression profiles in endometrioid endometrial cancers across 4 races. These proteins represent candidate biomarkers and drug targets for development of strategies to improve disparate outcomes of endometrial cancer patients.